Enhancer elements of compassion satisfaction in healthcare professionals - Buceta Toro, Maria Isabel; Bermejo Higuera, Jose Carlos; Villacieros Durban, Marta (Anales de Psicología / Annals of Psychology, 2019)
Objective: analysis of adult attachment styles, self-compassion, vocation, health care demands, caring satisfaction, job satisfaction and burnout on compassion satisfaction (CS) in healthcare professionals. Method: An online questionnaire was answered by 480 assistentially active healthcare professionals. Variables collected were socio-demographic, work experience, burnout and compassion satisfaction (ProQoL Quality of Life Questionnaire), self-compassion (by Neff), and attachment styles (Relation Questionnaire). Correlations, mean differences, multiple linear regression (MLR) and qualitative analysis of the emotional description of the job were analyzed. Results: A 79,6% (382) were women, age average 44,6 (DT = 10,86). CS score resulted significantly (p<,001) higher than burnout. Model for CS explained a 51.5% of the variability (correctedR2=,515); as predictor variables (p<,001), caring satisfaction (Beta=,309), vocation (Beta=,184), self-kindness (Beta=,158) and burnout (Beta=,306). Conclusions: compassion satisfaction is directly influenced by people caring satisfaction, vocation, self-kindness and absence of burnout. Indirectly also, by mindfulness capacity, feelings of common humanity, secure attachment style and satisfaction with the team. These also are preventing factors from burnout, that is directly related to concerned and fearful attachment styles and lack of self-compassion; self-judgement, over-identification and isolation.